All-pass filtering harmonic-eliminating structure and control method for intermediate-voltage power grid system - WU YI; LI QINGYUAN (2017)
The invention provides a full-pass structure, which is formed by fusing functional units of grounding equipment and compensation equipment, for the intermediate-voltage power grid system. A grounding loop of the grounding equipment serves to filter and eliminate low-frequency harmonic waves, and the reconstructed capacitive reactive compensation equipment serves to filter and eliminate other harmonic waves. The invention also provides a grounding control method in which the structure is used. Compared with the prior art, functions of filtering compensation equipment, grounding equipment, PT harmonic elimination equipment and a protective relaying device are combined, full-frequency filtering and harmonic elimination are realized, and a relay protection system realizes grounding control and grounding line-selection tripping. 本发明提供种用于中压电网系统的将接地设备和补偿设备功能单元融合改造成全通结构，其中由接地设备的接地回路组成对低频谐波的滤波消谐，由改造后的电容无功补偿设备实现对其它谐波的滤波消谐。本发明还提供了种应用该结构的接地控制方法。相比于现有技术，本发明将滤波补偿设备、接地设备、PT消谐装置以及继电保护装置四者功能融合起来，实现全频滤波消谐的同时由继电保护系统实现接地控制及接地选线跳